Students’ perceptions and lecturers’ practices as the basis for redesigning Mandatory Curriculum Courses (MKWK) based on OBE and SDGs - Fajar Nugraha; Dewang Sulistiana; Rahmat Rahmat (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2025)
The Compulsory Curriculum Courses (MKWK) play a strategic role in shaping graduates with Pancasila character. However, their implementation in higher education institutions still faces challenges related to relevance, teaching methods, and the integration of sustainability values. This study aims to analyze students’ perceptions and lecturers’ practices as the basis for redesigning the MKWK curriculum based on Outcome-Based Education (OBE) and the Sustainable Development Goals (SDGs) framework. A mixedmethods approach with a sequential explanatory design was employed. The quantitative phase involved a survey using a Likert-scale questionnaire administered to 204 students from various study programs at Universitas Muhammadiyah Tasikmalaya. The qualitative phase consisted of semistructured interviews with MKWK lecturers and selected students to explore and deepen the survey findings. The results revealed that students hold positive perceptions regarding the meaningfulness of MKWK values but rated low on innovation and diversity of teaching methods. In-depth interviews indicated the need for better alignment between learning outcomes (CPL), course learning outcomes (CPMK), and learning strategies that are more reflective and contextual. These findings provide a conceptual foundation for developing a new integrative MKWK syllabus based on OBE and SDGs, aimed at strengthening Pancasila character and 21st-century competencies among students. Keywords: curriculum, OBE, MKWK, SDGs